Primary percutaneous coronary intervention by drug-eluting balloon angioplasty: The nonrandomized fourth arm of the DEB-AMI (drug-eluting balloon in ST-segment elevation myocardial infarction) trial - Nijhoff, Freek; Agostoni, Pierfrancesco; Belkacemi, Anouar; Nathoe, Hendrik M.; Voskuil, Michiel; Samim, Mariam; Doevendans, Pieter A.; Stella, Pieter R. (Catheterization and cardiovascular interventions, 2015)
Objective To evaluate a paclitaxel drug‐eluting balloon (DEB) only strategy in primary percutaneous coronary intervention (PPCI), aiming at a comparison with bare metal stent (BMS) alone, DEB followed by BMS, and paclitaxel eluting stent (PES), as assessed in the randomized Drug Eluting Balloon in Acute ST‐Segment Elevation Myocardial Infarction (DEB‐AMI) trial. Background DEB‐only seems an attractive strategy in PPCI, as it obviates the risk of stent thrombosis. Methods This study is a prospective registry with the same inclusion/exclusion criteria used in the DEB‐AMI trial, as it constitutes the fourth, nonrandomized, treatment arm of this trial. Patients presenting with ST‐elevation myocardial infarction were allocated to DEB‐only (DIOR II, Eurocor GmbH, Bonn, Germany) after successful thrombus aspiration and predilatation. Primary endpoint was 6‐month angiographic in‐balloon/stent late‐luminal loss (LLL). Secondary endpoints were in‐balloon/stent binary restenosis and major adverse cardiac events (MACE: death, myocardial infarction, target‐vessel revascularization). Results Forty patients underwent PPCI by DEB‐only. Procedural success was achieved in 97.5% with bail‐out stenting required in 10.0% of procedures. In DEB‐only, LLL was 0.51 ± 0.59 mm as compared to 0.74 ± 0.57 mm in BMS (P = 0.44), 0.64 ± 0.56 mm in DEB+BMS (P = 0.88) and 0.21 ± 0.32 mm in PES (P < 0.01); in‐balloon/stent binary restenosis rates were 22.2%, 23.8% (P = 0.67), 28.6% (P = 0.97), and 4.5% (P = 0.07), respectively; and MACE rates were 17.5%, 23.5% (P = 0.20), 20.0% (P = 0.26), and 4.1% (P = 0.90), respectively. No acute or late thrombotic events occurred in the DEB‐only group. Conclusions PPCI by DEB‐only in selected patients yielded an angiographic outcome comparable to BMS alone and DEB followed by BMS. PES proved angiographic superiority to DEB‐only. DEB‐only is therefore a potential treatment alternative during PPCI in patients with contra‐indications to drug‐eluting stents. © 2015 Wiley Periodicals, Inc.